Superoxide dismutase promotes gastric tumorigenesis mediated by Helicobacter pylori and enhances resistance to 5-fluorouracil in gastric cancer - Hongbing Fu; Yu Zhang; Yantao Duan; Xin Zhang; Jun Yao; Dejun Yang; Ziran Wei; Zhenxin Zhu; Jiapeng Xu; Zunqi Hu; Qing You; Ronglin Yan; et al. (iScience)
Summary: Helicobacter pylori (H. pylori) infection is the most common risk factor for gastric cancer (GC). The effect of the antioxidase manganese superoxide dismutase (SOD2) in gastric tumorigenesis remains unclear. We explored the molecular mechanisms of links between H. pylori, inflammation, and SOD2 in GC. We found that SOD2 was upregulated in GC. GC patients with high SOD2 expression showed worse overall survival. H. pylori infection promoted SOD2 expression by transcriptionally activating the NF-κB signaling pathway. Knockdown of SOD2 led to increased levels of reactive oxygen species and oxidative stress in response to H. pylori infection. Our research demonstrates that SOD2 can serve as an inhibitor of ferroptosis by activating AKT, and stabilizing GPX4 protein, which subsequently induces 5-fluorouracil resistance. These findings reveal a mechanism whereby H. pylori can promote gastric carcinogenesis by activating the NF-κB/SOD2/AKT/GPX4 pathway, leading to the inhibition of ferroptosis. This may provide a promising therapeutic target for GC.